Information and Financial Literacy for Socially Sustainable NDC Pension Schemes - Fornero, Elsa (World Bank, Washington, DC, 2019)
This paper is centered on the complementary roles played by pension communication/information and financial literacy for a sustainable and equitable nonfinancial defined contribution (NDC) system at both the micro and macro socioeconomic level. The paper presents new evidence on: (i) the concern of public opinion about pensions in five European countries (France, Germany, Italy, Sweden, and the United Kingdom), as approximated by Google Trends data; (ii) the relationship between measures of online search volume and coverage by traditional media (i.e., national newspapers); and (iii) the volume and framing of newspaper coverage for a specific reform (i.e., the 2011 Italian reform). On the demand (users) side, the paper considers pension literacy as an element to increase the effectiveness of reforms.